2018
DOI: 10.1016/j.mce.2017.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of the androgen receptor in the central nervous system

Abstract: The involvement of gonadal androgens in functions of the central nervous system was suggested for the first time about half a century ago. Since then, the number of functions attributed to androgens has steadily increased, ranging from regulation of the hypothalamic-pituitary-gonadal axis and reproductive behaviors to modulation of cognition, anxiety and other non-reproductive functions. This review focuses on the implication of the neural androgen receptor in these androgen-sensitive functions and behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 125 publications
0
54
0
Order By: Relevance
“…In adult rodents, AR mRNA and protein are detected in neurons and glia of the medial amygdala, the preoptic area, the hypothalamus, the cerebellum, and the dentate gyrus of the hippocampus (Commins and Yahr, 1985 ; Sar et al, 1990 ; Hajszan et al, 2007 ; Feng et al, 2010 ; Pelletier, 2010 ; Mhaouty-Kodja, 2017 ). Interestingly, AR protein level is correlated with circulating levels of estradiol and testosterone across the estrous cycle, suggesting an estrogenic regulation of its expression (Feng et al, 2010 ).…”
Section: Steroid Signaling In the Brain: Focus On The Brains Of Fishmentioning
confidence: 99%
“…In adult rodents, AR mRNA and protein are detected in neurons and glia of the medial amygdala, the preoptic area, the hypothalamus, the cerebellum, and the dentate gyrus of the hippocampus (Commins and Yahr, 1985 ; Sar et al, 1990 ; Hajszan et al, 2007 ; Feng et al, 2010 ; Pelletier, 2010 ; Mhaouty-Kodja, 2017 ). Interestingly, AR protein level is correlated with circulating levels of estradiol and testosterone across the estrous cycle, suggesting an estrogenic regulation of its expression (Feng et al, 2010 ).…”
Section: Steroid Signaling In the Brain: Focus On The Brains Of Fishmentioning
confidence: 99%
“…The androgen receptor (AR) is similar in structure to the PRs, with a variable N-terminal transcriptional regulation domain, conserved DNA binding domain, and ligand binding domain (Mhaouty-Kodja, 2017 ). Also like PR, in the absence of hormones, the AR is complexed with chaperones in the cytosol.…”
Section: Sex Hormones and Receptors In The Cnsmentioning
confidence: 99%
“…Some studies have suggested that peripheral knockdown of the AR is sufficient to rescue disease phenotypes in SBMA mouse models [8,169]. Should these findings translate to patients, it would simplify drug delivery and spare androgen receptor function in the CNS [222]. However, there is also evidence that expression of the AR in the CNS drives disease [178,218].…”
Section: Sbma-open Questionsmentioning
confidence: 99%